Water Splitting: Why Tin‐Doping Enhances the Efficiency of Hematite Photoanodes for Water Splitting—The Full Picture (Adv. Funct. Mater. 52/2018). (27th December 2018) - Hufnagel, Alexander G.; Hajiyani, Hamidreza; Zhang, Siyuan; Li, Tong; Kasian, Olga; Gault, Baptiste; Breitbach, Benjamin; Bein, Thomas; Fattakhova‐Rohlfing, Dina; Scheu, Christina; Pentcheva, Rossitza
Abstract : Photoelectrical water oxidation by photoanodes comprised of ultrathin hematite films is investigated by Christina Scheu, Rossitza Pentcheva, and co‐workers in article number1804472 . It is determined that on‐surface tin doping prevents hole‐trapping and lowers the overpotential. Sub‐surface tin doping, provided the bulk remains undoped, introduces a band gradient, thereby enhancing charge separation efficiency. The results will be useful in developing high‐performance water splitting systems.